The distribution study of Ludai (Sapium SPP) in UiTM Jengka forest reserve (Base line 1: line 1 - line 5 and logging road) / Khadijah Khalid - Khalid, Khadijah (2005)
This study was carried out in (500m x 20m it will represent only 1% of the whole area of UiTMJFR.). The main objective of this study to know the distribution of Ludai (Sapium spp). We use Inventory method where we measure 10 meter (5 m right and 5 m left) and length are 515 meters. Beside that we have found about 44 % of Sapium spp which in Line 1 until Line 5 and Logging Road 33 % of individuals. The highest frequency of Sapium spp are in Line 1 which 28 of tree follow by Line 4, Line 5 Line 2 and the lowest are at Line 3 which 3 trees only. We also can see that 80% of Sapium spp was dominated by big tree (15-30 cm of DBH), and the rest are dominated by small pole (5-14 cm of DBH). For the pre mature tree DBH 31-45 and mature tree DBH >45 cm there are no tree have recorded. It means this area in secondary growth after logging, and it will log after 20 or 25 year later.